2018
DOI: 10.3926/jotse.356
|View full text |Cite
|
Sign up to set email alerts
|

Improving students' attitude, conceptual understanding and procedural skills in differential calculus through Microsoft mathematics

Abstract: This study examined the effects of using Microsoft Mathematics on students' attitude, conceptual understanding, and procedural skills in Differential Calculus. A quasi-experimental research design was used in which two different learning environments were compared. The participants of the study were two classes of Electrical Engineering students enrolled in Differential Calculus course, assigned randomly as control and experimental groups with 30 students in each group. The control group was taught using the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 35 publications
2
26
0
2
Order By: Relevance
“…The findings also conforms to the results of previous literatures and studies that the use of technology in teaching mathematics such as statistics may increase students' positive attitude towards the subject, and at the end will lead to better academic performance towards the subject (Mushtaq & Khan, 2012;Basturk, 2005;Zhang, et. al., 2012;Mendezabal & Tindowen, 2018;Mata, Monteiro & Peixoto, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The findings also conforms to the results of previous literatures and studies that the use of technology in teaching mathematics such as statistics may increase students' positive attitude towards the subject, and at the end will lead to better academic performance towards the subject (Mushtaq & Khan, 2012;Basturk, 2005;Zhang, et. al., 2012;Mendezabal & Tindowen, 2018;Mata, Monteiro & Peixoto, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Li et al (2014) justify the use of a matched-pair design for the same purpose. However, there is concern that some quasi-experimental studies, such as those of Mendezabal and Tindowen (2018) and Rosário et al (2017), use only random assignment without carrying out a pre-test evaluation of the degree of equivalence between their experimental groups, which in this type of design should be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, although we proposed to use the overall grade point average as a proxy measure of each student's PL, to apply the experiment to any subject, we believe we can improve this factor to balance the experimental groups by using the grade point average only of the subjects related to the topic taught (prerequisites), coinciding in this aspect with what is proposed by Mendezabal and Tindowen (2018), although differing in the assignment method, but this requires further assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Is there dialogue between the disciplines in the context of this research work? As regards to the first question, most of the articles considered were found to revolve around the design of some application or digital study material aimed at helping with the graphical visualization of concepts and favouring dynamic exploration through the interaction features offered by the digital media (Ascheri, Pizarro, Astudillo, García, & Culla, 2014;Dolecek, 2012;Gonzalez, Medina, Vilanova, & Astiz, 2011;Mendezabal & Tindowen, 2018). Several authors use applets (Aveleyra, Dadamia, & Racero, 2014;Ramírez Osorio, 2014) and animation (Morales, Herrera, Fennema, & Goñi, 2014;Pirro et al, 2012) as interactive resource.…”
Section: Bibliography Reviewmentioning
confidence: 99%